TI_GERICHTE 12.2008.236 vom 25. Juni 2009 , Diritto del lavoro. Licenziamento ingiustificato. abbandono del posto di lavoro - TI Tribunale d'appello (2009)
Diritto del lavoro. Licenziamento ingiustificato. abbandono del posto di lavoro